Inducing nematic ordering of cellulose nanofibers using osmotic dehydration. Issue 48 (5th December 2018) - Guccini, Valentina; Yu, Shun; Agthe, Michael; Gordeyeva, Korneliya; Trushkina, Yulia; Fall, Andreas; Schütz, Christina; Salazar-Alvarez, Germán
Abstract : The formation of nematically-ordered cellulose nanofiber (CNF) suspensions with an order parameter f max ≈ 0.8 is studied by polarized optical microscopy, small-angle X-ray scattering (SAXS), and rheological measurements as a function of CNF concentration. Abstract : The formation of nematically-ordered cellulose nanofiber (CNF) suspensions with an order parameter f max ≈ 0.8 is studied by polarized optical microscopy, small-angle X-ray scattering (SAXS), and rheological measurements as a function of CNF concentration. The wide range of CNF concentrations, from 0.5 wt% to 4.9 wt%, is obtained using osmotic dehydration. The rheological measurements show a strong entangled network over all the concentration range whereas SAXS measurements indicate that at concentrations >1.05 wt% the CNF suspension crosses an isotropic-anisotropic transition that is accompanied by a dramatic increase of the optical birefringence. The resulting nanostructures are modelled as mass fractal structures that converge into co-existing nematically-ordered regions and network-like regions where the correlation distances decrease with concentration. The use of rapid, upscalable osmotic dehydration is an effective method to increase the concentration of CNF suspensions while partly circumventing the gel/glass formation. The facile formation of highly ordered fibers can result in materials with interesting macroscopic properties.